Impact of digital technology investment on bank performance in Vietnam - Tien, Pham Phat; Tran, Ba Tri; Nguyen, Ngoc Duc; Nguyen, Thi Luong (Journal of Finance - Marketing Research, 2025)
This study examines the impact of digital technology investment on the performance of Vietnamese commercial banks, drawing on the productivity paradox theory proposed by Solow (1987), which suggests that technological progress may not immediately generate productivity gains. Panel data from 22 listed banks covering 2018–2023 were collected from disclosed statements. The Generalized Least Squares method was employed to estimate both contemporaneous and lagged effects of digital technology investment, with analysis spanning the pre-pandemic and COVID-19 periods. Results reveal that digital technology investment has a negative effect on bank performance in both periods, reflecting a paradoxical outcome where rising digital expenditures coincide with declining profitability. Evidence also suggests lagged effects, indicating that the benefits of digital adoption may materialize only in the longer term. The study enriches the literature by extending the productivity paradox debate to Vietnam, an emerging market undergoing rapid and policy-driven digitalization, while challenging the assumption that digital transformation consistently improves performance. Banks should enhance workforce digital skills, and policymakers should promote broader digital literacy to enable the sector to fully harness the transformative potential of technology for sustainable growth.